Abdominal obesity in Chinese patients undergoing hemodialysis and its association with all-cause mortality - Shi, Zhihua; Guo, Yidan; Ye, Pengpeng; Luo, Yang (Frontiers in Endocrinology, 2023)
Obesity in patients undergoing hemodialysis is common. however, there is limited information on the relationship between obesity types defined by the combined body mass index (BMI) and waist circumference (WC) classification criteria and all-cause mortality in Chinese hemodialysis patients. Our objective was to determine the association between obesity types and all-cause mortality in hemodialysis patients. We conducted a prospective cohort study including patients from 11 hemodialysis centers in Beijing. According to the World Health Organization's standards, patients were classified into 2 categories with WC and 4 categories with BMI and then followed up for 1 year. Kaplan–Meier survival analysis was used to compare the difference in the cumulative survival rate in different BMI and WC groups. A multivariate Cox regression analysis was used to determine the association between different types of obesity and all-cause mortality. A total of 613 patients were enrolled, the mean age was 63.8 ± 7.1 years old, and 42.1% were women. Based on the baseline BMI, there were 303 (49.4%) patients with normal weight, 227 (37.0%) with overweight, 37(6.0%) with obesity, and 46 (7.5%) with underweight. Based on the baseline WC, there were 346 (56.4%) patients with abdominal obesity. During a median follow-up of 52 weeks, 69 deaths occurred. Kaplan–Meier plots demonstrated a significant association of BMI categories (log-rank ꭓ2=18.574, p<0.001) and WC categories (log-rank ꭓ2=5.698, p=0.017) with all-cause death. With normal BMI and non-abdominal obesity as a reference, multivariate Cox regression analysis results showed that obesity (HR 5.36, 95% CI, 2.09-13.76, p<0.001), underweight (HR, 5.29, 95% CI, 2.32-12.07, p<0.001), normal weight combined with abdominal obesity(HR 2.61, 95% CI, 1.20-5.66, p=0.016 ), and overweight combined with abdominal obesity (HR 1.79, 95% CI, 1.03-3.73, p=0.031, respectively) were significantly associated with higher risks of all-cause mortality. Our study indicated that abdominal obesity is common and associated with all-cause mortality among Chinese patients undergoing hemodialysis.